The Design of A Coffee Pulper Machine By Using Inventor Autocad Software - Sutopo; Khairul Irsad (Journal of Applied Mechanical Engineering Innovation, 2025)
Coffee is one of the favorite beverages enjoyed by people from all walks of life. The main challenge in the coffee bean peeling process in small and medium enterprises (SMEs) is that it is still done manually. The primary goal of creating this technological innovation is to assist workers in the production process by using appropriate technology, thereby improving the quality, effectiveness, and efficiency of their work. The design optimization and manufacturing process of the coffee pulper machine begins with literature studies, design and calculations, the fabrication of the machine, and ends with testing. The design is created using Inventor Autocad software. The coffee peeling machine measures 110 cm x 127 cm x 130 cm and is powered by a gasoline engine with an initial speed of 1800 rpm, which increases to 3600 rpm. It uses two pulleys with a ratio of 1:6, an A-75 V-belt, and a solid shaft with a diameter of 20 mm. The final result shows that the coffee pulper machine has a capacity of 610 kg per hour.